Edukasi Pemanfaatan Tanaman Serai sebagai Biopestisida untuk Pengendalian OPT di Desa Tanjung Dayang Selatan Kab. Ogan Ilir, Sumatera Selatan - Ika Paridawati; Nurbaiti Amir; Delfy Lensari; Berliana Palmasari; Dessy Tri Astuti; Fairuz Haiva Zahra Alamsyah (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
Controlling Plant Pest Organisms (OPT) remains a major challenge for farmers in Tanjung Dayang Selatan Village, Ogan Ilir Regency (OI). Continuous use of chemical pesticides has the potential to negatively impact the environment, health, and reduce the quality of agricultural products. Therefore, more environmentally friendly alternatives for controlling PESTs are needed through the use of natural materials, one of which is lemongrass (Cymbopogon citratus) as a biopesticide. This educational activity aims to increase community knowledge and skills in utilizing lemongrass as a natural biopesticide. The activity method is carried out through counseling, demonstrations of biopesticide production, and direct practice of using lemongrass solutions on agricultural crops. The results of the activity show an increase in community understanding of the benefits of lemongrass as a natural pest control and an increase in farmer interest in applying biopesticides to their agricultural land. The use of lemongrass as a biopesticide is considered effective, easy to make, economical, and safer for the environment than chemical pesticides. With this education, it is hoped that the community will be able to implement sustainable agriculture and reduce dependence on synthetic pesticides for PEST control.